Thermal and morphological properties of human erythrocytes from patients afflicted with type 1 diabetes mellitus - Péter Gaszler; Dénes Lőrinczy; Dávid Szatmári; Beáta Bódis; Katalin Türmer (Heliyon)
Red blood cells (RBC), are the most unique and abundant cell types. The diameter of RBCs is 7–8 μm. They have an essential role in transporting circulatory oxygen. The RBCs travel through varioussized capillaries throughout the entire body, some significantly smaller than the RBCs due to their incredible deformability. The RBC membrane allows the cell to resist stress as it squeezes the cytoplasm. Permanent stress or altered blood plasma conditions can result in decreased membrane deformability. Type 1 diabetes mellitus (T1DM) is one of the most common chronic diseases. In diabetes, the primary influence is increased glucose levels in the blood plasma that can result in the oxidation of lipids and proteins and the glycation of proteins. The damage changes the conformation and organization of various lipids and proteins, which can result in the loss of function and decreased deformability. Hemoglobin A1c (HbA1c) or glycohemoglobin is a form of hemoglobin found in RBCs. Glucose and fructose can bind to hemoglobin by non-enzymes, and different glycated forms of hemoglobin can be formed. The ratio of glucose-bound (glycated) hemoglobin to total hemoglobin (expressed as a percentage) is a critical laboratory parameter in managing diabetes. It can be used to determine the average blood glucose level of the patient over the past 60–120 days. Here, we investigate the effect of diabetes on RBCs’ shape and membrane stability due to microscopy and DSC (Differential Scanning Calorimetry) methods. The comparison of the RBCs from diabetic and non-diabetic patients was classified by the HbA1c, showing that the conditions in diabetes caused atypical cell morphology and then, in a casedependent manner, increased or decreased the thermal stability of cytoplasm or the cell membrane, respectively. It shows the importance of DSC application in routine quality screening of diabetic erythrocytes and that it can be a crucial parameter of T1DM.